Local oestrogen therapy and the risk of neoplasmatic disease - Rechberger, Tomasz; Kokot, Marta; Bartuzi, Aleksandra; Wróbel, Andrzej (Menopause Review/Przegląd Menopauzalny, 2008)
Local oestrogen therapy is regarded as the therapeutic standard in the treatment of urogenital atrophy. In women treated previously due to non-hormone-dependent tumours, urogenital atrophy treatment is similar to that in patients without cancer in the past with the exception of those who were subjected to radiotherapy of the pelvis. In this group local, low-dose oestrogen therapy is indicated in order to stimulate regeneration of epithelium, improvement of flexibility and lubrication of the vaginal wall. The first line of treatment in patients suffering from urogenital atrophy with hormone-dependent tumours in anamnesis consists of vaginal lubricants and moisturizers, but local oestrogen could also be considered after consultation with an oncologist. On the other hand, because of the fact that systemic absorption of oestrogens from low-dose vaginal tablets is minimal, it may be supposed with high probability that the possible promotional effect of neoplastic recurrence would be minimal.